1970
DOI: 10.3329/bjvm.v6i2.2332
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bovine tuberculosis and its effects on milk production in Red Chittagong cattle

Abstract: Bovine tuberculosis (bTB) is one of the most prevalent economically important zoonotic diseases and tuberculin test has been widely used to detect its prevalence worldwide. This study used a commercial immunochromatographic assay (ICGA) to detect the prevalence of bTB and to evaluate the differences in milk production between lactating cows with positive and negative results in Bangladesh. Thirty Red Chittagong (indigenous) cattle (RCC) were randomly selected from a herd of 87 RCC maintained at the Bangladesh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

1970
1970
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 3 publications
0
17
1
Order By: Relevance
“…The overall prevalence (5.9%) of bovine TB reported in this study is comparable with the reports of Pharo et al (1981) and Samad and Rahman (1986). However, it was lower than the reports of Rahman and Samad (2008), Ameni et al (2007), Islam et al (2007) and Swai et al (2006). The differences may be due to size of the sample, type of diagnostic test used, husbandry system etc.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…The overall prevalence (5.9%) of bovine TB reported in this study is comparable with the reports of Pharo et al (1981) and Samad and Rahman (1986). However, it was lower than the reports of Rahman and Samad (2008), Ameni et al (2007), Islam et al (2007) and Swai et al (2006). The differences may be due to size of the sample, type of diagnostic test used, husbandry system etc.…”
Section: Resultscontrasting
confidence: 56%
“…The prevalence of bTB in cattle has been reported as 5.9% and 3.05% in Pabna and Mymensingh district, respectively (Pharo et al, 1981;Samad and Rahman, 1986) while, in breeding bull it is reported as 27.5% (Islam et al, 2007). However, recent study showed 30% prevalence of bTB in Red Chittagong cattle (Rahman and Samad, 2008 Enzyme Linked Immunosorbent Assay (ELISA), immunochromatographic assay (ICGA), Latex bead agglutination assay (LBAA) and PCR (Jark et al, 1997;Costello et al, 1998;Valente et al, 1997;Aranaz et al, 1996). Among them tuberculin test has been frequently used for the screening purpose (Islam et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The Red Chittagong cattle (RCC) are the only recognized cattle variety available in Bangladesh. But very limited research works on production Mufti et al, 2009;Rabeya et al, 2009) and health especially on bovine tuberculosis (Rahman and Samad, 2008) and effects of endoparasites on blood values (Siddiki et al, 2010) have been done in this variety of cattle. This study describes the prevalence of sub-clinical gastro-intestinal parasitosis and their effects on milk production with therapeutic management in RCC maintained under farming system.…”
Section: Introductionmentioning
confidence: 99%
“…Production losses will vary, both between infected animals and infected herds. Studies have found that bTB was associated with a 18% decrease in milk production in cattle in Bangladesh (Rahman and Samad, ) and 4% in USA (Hernandez and Baca, ). Bovine tuberculosis has been reported to decrease meat production by 6–12% (± 2.5%), depending on the percentage of cows (30–70%) in a herd in which more than 80% of all animals or more than 95% of cows are infected (Zinsstag et al., ).…”
Section: Assessmentmentioning
confidence: 99%